2018
DOI: 10.4314/tjpr.v17i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Properties of <i>Clinacanthus nutans</i>: A review

Abstract: To date, medicinal plants are the most important resources in the discovery of new drugs. Clinacanthus nutans has been used traditionally in Thailand folk medicine to promote overall well-being. A few biological constituents of C. nutans and their physiological functions have been evaluated in previous studies. However, the mechanisms of action, potency and efficacy of the plant are still not well understood. In this review, the pharmacological properties of C. nutans such as anti-inflammatory effects, anti-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Clinacanthus nutans is a medicinal plant that has many medicinal properties, including treating lesions generated by the herpes-simplex virus, antiinflammatory, anticancer, antibacterial, and antivenom activities [7]. C. nutans is found in Malaysia, Vietnam, Indonesia, Thailand, and China [8,9], and occurs in most habitats [10].…”
Section: Introductionmentioning
confidence: 99%
“…Clinacanthus nutans is a medicinal plant that has many medicinal properties, including treating lesions generated by the herpes-simplex virus, antiinflammatory, anticancer, antibacterial, and antivenom activities [7]. C. nutans is found in Malaysia, Vietnam, Indonesia, Thailand, and China [8,9], and occurs in most habitats [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both clinacosides showed anti-neuroinflammatory effects against lipopolysaccharide (LPS)-induced neurotoxicity in the in vivo rat model [9]. Furthermore, they displayed inhibitory effects towards human neutrophil elastase enzymes in silico, which indirectly signified their abilities to prevent inflammation in the respiratory system [13,52]. Based on their proven antioxidative and anti-inflammatory potentials, these three compounds are indeed promising hepatoprotective agents that warrant further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their proven antioxidative and anti-inflammatory potentials, these three compounds are indeed promising hepatoprotective agents that warrant further investigations. Among the three compounds, isoschaftoside is the most stable phytochemical detected in C. nutans from different geographical locations, regardless of the environmental conditions [13]. Thus, it is deemed a suitable chemical marker to standardize C. nutans extract or even raw materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a non-scientific and unpublished survey of ethnobotanical applications of medicinal plants has demonstrated that C. nutans rated amongst the top five most commonly used herbs for anti-diabetic, anti-hypertensive, anti-inflammatory and antioxidant properties in other sub-tropical countries such as in Malaysia, Brunei and Singapore. Other pharmacological activities such as anti-venom, anti-cancer, anti-bacterial, anti-fungal and anti-analgesic activities have also been reported [ 10 , 20 , 37 ].…”
Section: Pharmacological and Medicinal Propertiesmentioning
confidence: 99%